Recognition of Bacillus subtilis receptors by bacteriophage SPP1 : a genetic and biochemical approach - Baptista, Catarina Duarte Galhardo, 1979- (2009)
Tese de doutoramento, Biologia (Biologia Molecular), Universidade de Lisboa, Faculdade de Ciências, 2009